Evaluation of anxiety of medical personnel during the coronavirus outbreak in Tasikmalaya, Indonesia - Tetet Kartilah; Aan Komariah; Saurabh Singhal; Mohammad Javed Ansari; Muneam Hussein Ali; Supat Chupradit; Abduladheem Turki Jalil; Mazin A.A. Najm; A. Heri Iswanto (International Journal of Body, Mind and Culture, 2022)
Background: Coronaviruses are a large family of viruses that can cause respiratory infections. A factor that has recently caused a great deal of anxiety is anxiety associated with the coronavirus. The purpose of this study was to evaluate the level of anxiety among medical personnel exposed to the new coronavirus pandemic.